Broadband dielectric and ultrasonic properties of WS2 nanotubes/polyurethane composites. Issue 12 (24th August 2017) - Macutkevic, J.; Belovickis, J.; Otorgust, G.; Dodiuk, H.; Kenig, S.; Samulionis, V.; Banys, J.; Zak, A.
Abstract : Broadband dielectric properties of tungsten disulfide (WS2 ) nanotubes/polyurethane (PU) composites over a wide temperature range (300 K–450 K) are presented for concentrations up to 2 wt%. Although no electrical percolation was observed in composites, at room temperature the dielectric permittivity of thermosetting composites with 2 wt% inclusions is 2 times higher than the dielectric permittivity of the pure polymer, that indicate that the composites are suitable for antistatic applications. Broadband dielectric properties of the composites are mainly governed by the α relaxation, the dynamics of the "soft" molecular segment of the PU chain. The Vogel temperature decreases with increase in the concentration of the WS2 nanotubes. At higher temperatures (above 380 K) the electrical conductivity dominates in properties of pure PU and composites with the WS2 inclusions as well. The DC conductivity increases with the WS2 concentration in thermosetting composites, while its activation energy is almost independent from the WS2 concentration far from melting point. The DC conductivity has some change in slope close to 420 K. Above room temperature, the large ultrasonic relaxational attenuation maxima and the velocity dispersion were observed. It was found that the attenuation peak in composites shifted to lower temperatures after addition of nanoparticles. The ultrasonic attenuation data of thermosetting composites were fitted to the relaxation equation with the single temperature‐dependent relaxation time. The thermal activation energy of the relaxation process, which was calculated from the ultrasonic data, was found to increase in PU with the concentration of WS2 nanotubes. POLYM. COMPOS., 39:4477–4485, 2018. © 2017 Society of Plastics Engineers